Whale fall - O'Connor, Elizabeth, 1991- (Pantheon Books, 2024)
"In 1938, a dead whale washes up on the shores of remote Welsh island. For Manod, who has spent her whole life on the island, it feels like both a portent of doom and a symbol of what may lie beyond the island's shores. A young woman living with her father and her sister (to whom she has reluctantly but devotedly become a mother following the death of their own mother years prior), Manod can't shake her welling desire to explore life beyond the beautiful yet blisteringly harsh islands that her hardscrabble family has called home for generations. The arrival of two English ethnographers who hope to study the island culture, then, feels like a boon to her--both a glimpse of life outside her community and a means of escape. The longer the ethnographers stay, the more she feels herself pulled towards them, reckoning with a sensual awakening inside herself, despite her misgivings that her community is being misconstrued and exoticized. With shimmering prose tempered by sharp wit, Whale Fall tells the story of what happens when one person's ambitions threaten the fabric of a community, and what can happen when they are realized. O'Connor paints a portrait of a community and a woman on the precipice, forced to confront an outside world that seems to be closing in on them"--